Quality of Care of Young People Presenting With Self-Harm at the Norfolk and Norwich University Hospital Emergency Department - Bolanle Mojibola; Ayomipo Amiola; Tosin Daropale (BJPsych Open)
Aims: To determine the quality of care received by young people (16–25 years) presenting with self-harm at the Norfolk and Norwich University Hospital Emergency department using NICE guidelines QS34.